Digital Portfolio As A Tool For Developing Self-Presentation And Communicative Skills (Eurasian Journal of Learning and Academic Teaching, 2025)
The article examines the role of the digital portfolio as a modern pedagogical tool that contributes to the development of students’ self-presentation, communication, and metacognitive skills. The author emphasizes that the integration of the electronic portfolio into the educational process enables a shift from traditional forms of assessment to a reflective and developmental approach aimed at forming the professional identity of future specialists. The digital portfolio is viewed not only as a tool for recording academic achievements but also as a space for self-development, critical analysis, and communication among participants in the educational process. Particular attention is given to the impact of digital technologies on enhancing motivation, fostering selfreflection skills, and developing a culture of written and visual communication among students.